Digital Innovation Seizing Policy Opportunities - OECD (OECD Publishing, 2019)
This report discusses how the digital transformation - digital technologies, data and software, AI-based analytics and other advances - is changing innovation processes and outcomes. It highlights the general trends across the economy and factors behind sector-specific dynamics, including increasing use of data as a key input for innovation, the expanding possibilities for experimentation offered by virtual simulation, 3D printing and other digital technologies, and the growing focus on services innovation enabled by digital technologies.